Strength Analysis of Composite Material Wheels - Jiang Pengfei; Mi Caiying (机车电传动)
A composite material wheel structure of aluminum alloy wheel core and steel wheel rim was developed. The mass ofthe structure was less than 25% of the traditional steel wheel, which could effectively reduce the unsprung mass. The FE model of thecomposite material wheel was created in the ANSYS software, and then static and fatigue strength of the structure were analyzed based onUIC510-5 standard and DVS 1608 standard. The results was shown as follows: compared with the traditional steel wheel, the compositematerial wheel of aluminum wheel core has lower radial stiffness; the wheel core bears mainly compressive stress in the process of trainoperation, which makes full use of advantage of aluminum alloy material’s compressive performance, and guarantees that the static andfatigue strength properties of aluminum alloy wheel core are the same as the steel wheel.